2014
DOI: 10.1007/s10806-014-9527-6
|View full text |Cite
|
Sign up to set email alerts
|

Current Agricultural Practices Threaten Future Global Food Production

Abstract: In future decades, food demand for an increased population with elevated standards of living poses a huge challenge, particularly in the sense of the environmental impacts of agricultural systems. We have analyzed agricultural data from the past 50 years, and found that the current agricultural practices will have negative effects on global food production: total agricultural area has decreased since 2000, fertilizer and pesticide consumption increased while their efficiency decreased, and available water sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Foliar application of pesticides as the major management practices to control pests and diseases has been widely used worldwide to increase crop production (Liu et al, 2015). Recently, there has been much interest in the incorporation of Zn into the routine spraying of foliar pesticide (Ram et al, 2016), with the rationalization that this practice will be more economical and adoptable by farmers due to the elimination of extra labor or machinery input.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Foliar application of pesticides as the major management practices to control pests and diseases has been widely used worldwide to increase crop production (Liu et al, 2015). Recently, there has been much interest in the incorporation of Zn into the routine spraying of foliar pesticide (Ram et al, 2016), with the rationalization that this practice will be more economical and adoptable by farmers due to the elimination of extra labor or machinery input.…”
mentioning
confidence: 99%
“…Although one previous study showed that mixed foliar application of Zn and pesticides was as effective as foliar Zn alone in increasing grain Zn, only insecticides controlling aphid were tested (Wang et al, 2015b), leaving it unanswered whether foliar Zn applied together with various pesticides would affect grain Zn concentration. This issue is important because wheat is commonly attacked by other foliar diseases (e.g., head blight, powdery mildew, and leaf rust) and pests (e.g., midge and red spider mite) (Liu et al, 2015). Various kinds of insecticides and fungicides are therefore annually sprayed on wheat plants (Brauns et al, 2018).…”
mentioning
confidence: 99%
“…Now some tell us that current agricultural practices may threaten future global food security and will have negative effects on global food production [8]. The total agricultural area has decreased since 2000, fertilizer and pesticide consumption have increased, water use efficiency has increased, and available water sources are already being used for irrigation.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Industrial agricultural production methods used in Australia may not guarantee food security [92,93]. The sustainability of modern agricultural production is in question in Australia and internationally especially as intensification is likely to lead to a tradeoff between production and more environmental damage [94]. The level of relative poverty in Australia [46], especially among children, contrasts with traditional Australian values of mateship and empathy [95,96].…”
Section: Control Issues Includementioning
confidence: 99%